Jean Porter, Nature as Reason. A Thomistic Theory of the Natural Law, Grand Rapids, Eerdmans, 2005, 420 pp. - Irrazábal, Gustavo Roque (2007)
Fil: Irrazábal, Gustavo Roque. Investigador independiente; Argentina